2018
DOI: 10.3892/mmr.2018.9605
|View full text |Cite
|
Sign up to set email alerts
|

Long term exposure to γ‑rays induces radioresistance and enhances the migration ability of bladder cancer cells

Abstract: In Western countries, bladder cancer (BCa) is one of the most common types of malignancy, with highest incidence rate among urinary system malignancies. At present, as a strategy to preserve the quality and function of the bladder tissues, external-beam radiotherapy has been applied to an increasing number of patients with BCa, particularly the elderly and those in poor health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
2
3
0
Order By: Relevance
“…Moreover, our results are also consistent with the reported accelerated repopulation after clinical radiotherapy (49). In our study, radioresistant cells also exhibited increased migration and anti-apoptotic ability, consistent with previous reports (50). Interestingly, the morphology changes observed in NF639R cells, including reduction and elongation of cell bodies, are similar to the cells undergoing epithelial-mesenchymal transition (EMT).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our results are also consistent with the reported accelerated repopulation after clinical radiotherapy (49). In our study, radioresistant cells also exhibited increased migration and anti-apoptotic ability, consistent with previous reports (50). Interestingly, the morphology changes observed in NF639R cells, including reduction and elongation of cell bodies, are similar to the cells undergoing epithelial-mesenchymal transition (EMT).…”
Section: Discussionsupporting
confidence: 93%
“…3A). Consistent with previous reports (18,19), increased levels of pSTAT3 and MMP-2/9 were detected in both RR cell types. Also, the differences in two STAT3-based CSC-related signaling pathways, [KMT1A/GATA3/STAT3 (21) and JAK/STAT3 (27)] were assessed between parental BCa cells and their RR counterparts.…”
Section: Elevated Stat3 Phosphorylation In Rr Bca Cells Is Associatedsupporting
confidence: 93%
“…Our previous study reported that FI increases STAT3 phosphorylation in BCa cells (18). STAT3 phosphorylation also suppressed the RR of glioblastoma stem cells, and was associated with improved patient prognosis (33).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to explore the mechanism of BCa recurrence and treatment tolerance after clinical radiotherapy, we established ARR cell model 5637R and T24R ( Fig. 1 A) by subjected human BCa cell lines 5637 and T24 to long-term IR as described previously [11] . With tumor microsphere culture and soft agar colony anchoring assay, we noticed that ARR cells (5637R & T24R) exhibited enhanced CSC properties compared to the parental cells (5637 & T24), respectively.…”
Section: Resultsmentioning
confidence: 99%